Stability of vacuum and nonvacuum-packed corned native chicken (Gallus gallus) at different temperatures - Jungco, Ramelyn Alarcon (2006.)
Corned native chicken samples were packed in polyethylene plastic bags using vacuum and nonvacuum packaging methods.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Corned native chicken; Gallus gallus